Learnings from select Indian public welfare programs to catalyze the implementation of India’s national actional plan on antimicrobial resistance - Joshi, Jyoti; Kotwani, Anita (International Journal Of Community Medicine And Public Health, 2021)
Antibiotics are an easy, rapid and quick replacement to improved care within fragmented health systems with poor access and infection control measures in many countries, including India. India announced its national action plan for antimicrobial resistance (NAP-AMR) 2017-2021 but has made limited progress. Successful public welfare programs (Delhi metro rail corporation DMRC, swachh bharat mission (SBM), beti bachao beti padao (B3P) and national green tribunal NGT) were reviewed that had addressed critical national concerns similar to AMR. Valuable lessons from their implementation provide the opportunity to improve the governance and operationalization of the NAP-AMR. Unique features of the four programs identified above include resilient leadership, multi-stakeholder coordination with oversight and accountability of partnerships, innovation in program design and implementation and data-driven real-time monitoring for sustained behavior change. Incorporating these strategies into the program design and implementation of India’s NAP-AMR will reinvigorate the program to accelerate the achievement of program targets.